Distribution of Hepatitis B Infection in Cleaning Services in Manado City, North Sulawesi - Makaminan, Muhammad Ali; Makalew, Linda Agustine; Sumenge, Dionysius; Lalangpuling, Indra Elisabet (UNUSA Press, 2025)
Introduction: Hepatitis B is a disease caused by a viral infection and can be easily transmitted. Hospitals can be one of the places where Hepatitis B is transmitted. Hospitals produce waste that can be a source of transmission for several professions, both health workers and cleaning services or cleaning staff in hospitals because they are in direct contact with the source of Hepatitis B virus transmission. Objective: This study aims to determine the description of the results of Hepatitis B examinations on cleaning service staff at hospitals in Manado, North Sulawesi. Methods: This type of research is descriptive. With a random sampling technique. The samples found were 164 samples that met the sample criteria, then examined using the ELISA method. The results were declared positive for HBsAg if they exceeded the cut-off value obtained from the average value of the negative control. The data obtained are presented in table form and narrated descriptively. Results: The research results show that there are more female respondents than male respondents, namely 94 people (57.3%) with a greater age range above 36 years (60.4%) with a working period of less than 10 years (62.8%). More respondents with less knowledge of hepatitis B and many have not been vaccinated (82.9%). And it was found that the use of complete PPE was around 108 (65.9%) respondents. 4 (2.4% ) respondents obtained the results of the examination using the ELISA method that exceeded the cut-off value. Conclusions: The conclusion of this study is that 2.4% of respondents were positive for Hepatitis B and all worked at Prof. Dr. R. D Kondou Hospital.